2016
DOI: 10.1111/cmi.12616
|View full text |Cite
|
Sign up to set email alerts
|

LC3-associated phagocytosis: a crucial mechanism for antifungal host defence againstAspergillus fumigatus

Abstract: Summary LC3‐associated phagocytosis (LAP) is a non‐canonical autophagy pathway involved in the maturation of single‐membrane phagosomes and subsequent killing of ingested pathogens by phagocytes. This pathway is initiated following recognition of pathogens by pattern recognition receptors and leads to the recruitment of LC3 into the phagosomal membrane. This form of phagocytosis is utilized for the antifungal host defence and is required for an efficient fungal killing. Here, we provide an overview of the LAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 87 publications
(161 reference statements)
0
34
0
Order By: Relevance
“…We found that IFN-γ not only mediated LAP to A. fumigatus but also regulated NLRP3 activation during infection. The importance of LAP for fungal clearance (Kyrmizi et al., 2013, Martinez et al., 2015, Sprenkeler et al., 2016) and its subversion by fungal melanin (Akoumianaki et al., 2016) have been recently described. However, inflammation has to be controlled under microbial autophagy in the lung to prevent pulmonary overreaction (Kanayama et al., 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…We found that IFN-γ not only mediated LAP to A. fumigatus but also regulated NLRP3 activation during infection. The importance of LAP for fungal clearance (Kyrmizi et al., 2013, Martinez et al., 2015, Sprenkeler et al., 2016) and its subversion by fungal melanin (Akoumianaki et al., 2016) have been recently described. However, inflammation has to be controlled under microbial autophagy in the lung to prevent pulmonary overreaction (Kanayama et al., 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…LAP-deficient mice develop an auto-inflammatory, lupus-like syndrome with aging, which can be recapitulated by chronic exposure to apoptotic cells [7]. Also, LAP-deficient mice fail to efficiently clear Aspergillus fumigatus infection [17, 89]. Thus, it is clear that defects in the LAP mechanism can have a breadth of immunological consequences.…”
Section: Lap Promotes Differential Outcomes During Immune Activationmentioning
confidence: 99%
“…nidulans Phagosomes containing Aspergillus conidia mature into a phagolysosome, a process that is characterized by fusion with endosomes and lysosomes. Over the past years it has been demonstrated that a fully functional LAP is required for inducing an optimal phagosome maturation of phagosomes containing A. fumigatus by monocyte/macrophages [19][20][21][22]. Moreover, cells from CGD patients recruit LC3 to Aspergillus-containing phagosomes less efficiently [7,20].…”
Section: Lc3-associated Phagocytosis Is Less Efficient Formentioning
confidence: 99%